Determining the role of SGLT2 inhibitors (dapagliflozin) on progression of proteinuria among non-diabetic adult patients with chronic kidney disease: a randomized controlled trial - Srivastava, Shivam; Agarwal, Saurabh; Gulati, Yuvraj; Singh, Alok Kumar; Aggarwal, Prakhar (International Journal of Advances in Medicine, 2025)
Background: In patients with type 2 diabetes, SGLT2 inhibition lowers albuminuria and the risk of renal disease progression. Improvement in glycemic control is unlikely to be the only factor mediating these advantages. The goal of this study was to determine any possible benefit of the SGLT2 inhibitor among subjects with non-diabetic kidney disease. To determine the effect of SGLT2 inhibitor (Dapagliflozin) on proteinuria among subjects with non-diabetic kidney disease. Methods: A randomized control trial was conducted at K.P.S PG institute of medicine in association with Department of Nephrology, GSVSPGI, GSVM medical college, Kanpur. Eligible subjects were adult patients with non-diabetic CKD with eGFR between 25-90 ml/min/1.73m2 and having proteinuria with urinary albumin creatinine ratio (ACR)>30 mg/g for more than 3 months. Subjects were randomized to receive either dapagliflozin (10 mg) or placebo. Results: A total of 228 subjects were screened between June 2022 to May 2023. Sixty-seven subjects met the inclusion criteria and only 46 subjects consented to participate in the study. The subjects were randomized in 1:1 ratio to receive either intervention or placebo for duration of 6 months. At the end of 6 months study period the intervention group demonstrated a median (IQR) reduction of-9.99(-63.17 -(-4.78)) mg/g (p value<0.01) in ACR along with a median (IQR) increase in eGFR of 19.23 (3.85-23.81) ml/min/1.73m2 from baseline. The placebo group continued to show a constant decline in eGFR with a median reduction of -32.43 (-59.8- (-23.04)) ml/min/1.73m2 from baseline with no significant change in ACR. Conclusions: Use of SGLT2i among subjects with non-diabetic kidney disease resulted in reduction of proteinuria and an improvement in the real function. Therefore, SGLT2i may also be used among patients with non-diabetic kidney disease to check its progression.